Efficiency of specific anti-inflammatory therapy in complex treatment of pregnant women with the pathological vaginal discharge syndrome - С. Н. Бакшеєв; А. В. Кузьміна; Н. В. Машир (Publishing House TRILIST, 2019)
Vaginal discharge during pregnancy is common, but pathological vaginal discharge must be distinguished from pregnancy leukorrhea, which is normal throughout pregnancy and increases with gestational age. At pregnancy the vaginal mucosa becomes thinner and has a large surface area, which makes pregnant women more susceptible to infections. This is leads to the abnormal vaginal discharge, which in most cases is associated with a local inflammatory process. Based on this it can be concluded that antibiotic therapy alone is aimed only at the inflammation etiology, and does not allow to impact on its pathogenesis. A prospective short-term study of 90 pregnant women aged from 25 to 41 years with the syndrome of pathological vaginal discharge was done. Pregnant women were divided into groups depending on the treatment: Group I - 30 patients who received antimicrobial therapy for 12 days; Group II - 30 patients who received antimicrobial therapy for 12 days in combination with the anti-inflammatory drug Tantum Rosa® during 7 days; Group III - 30 patients who received antimicrobial therapy for 12 days in combination with Tantum Rosa®, used for 7 days. After the end of treatment patients of group III received an anti-relapse course of Tantum Rosa® (1 flacon twice a week) for three months to eliminate local inflammation. Study results showed that combination therapy with a specific anti-inflammatory drug (Tantum Rosa®) and antimicrobial drug more effectively eliminates acute symptoms and prevents relapse than monotherapy with an antimicrobial agent; additional prescription of the prophylactic course Tantum Rosa® after the end of the main therapy course is effectively prevents the pathological vaginal discharge syndrome recurrence. This is due that benzydamine hydrochloride, which is active substance of Tantum Rosa®, is a powerful inhibitor of anti-inflammatory cytokines.